Gold nanoparticles: Opportunities and Challenges in Nanomedicine - Arvizo, Rochelle (2010)
IMPORTANCE OF THE FIELD: Site-specific drug delivery is an important area of research that is anticipated to increase the efficacy of the drug and reduce potential side effects. Due to this, substantial work has been done developing non-invasive and targeted tumor treatment with nano-scale metallic particles. AREAS COVERED IN THIS REVIEW: This review focuses on the work done in the last several years developing gold nanoparticles as cancer therapeutics and diagnostic agents. However, there are challenges in using gold nanoparticles as drug delivery systems such as biodistribution, pharmacokinetics, and possible toxicity. Approaches to limit these issues are proposed. WHAT THE READER WILL GAIN: Different approaches from several different disciplines are discussed. Potential clinical applications of these engineered nanoparticles is also presented. TAKE HOME MESSAGE: Because of their unique size-dependent physico-chemical and optical properties, adaptability, sub-cellular size, and bio-compatibility, these nanosized carriers offer an apt means of transporting small molecules as well as biomacromoleculs to diseased cells/ tissues.